Failure Mechanism of the Qianjiangping Slope in Three Gorges Reservoir Area, China - Zhenhua Zhang; Mingming Qian; Song Wei; Juxiang Chen (Geofluids)
The Qianjiangping landslide is the first large-scale rock slide in Three Gorges Reservoir (TGR) Area, China, after the impoundment of the TGR. Previous studies on the slope showed that most researchers agreed that reservoir impoundment and rainfall were the two main triggering factors of the slope failure. However, there were different views about the influence degrees of the two factors on the slope failure. In order to clarify the influence degrees of each of three conditions (reservoir impoundment, rainfall, and combined effect of reservoir impoundment and rainfall) on the failure of the Qianjiangping slope and reveal the failure mechanism of the slope, underground water tables and stresses in the slope were calculated under the three conditions, respectively, based on fluid-solid coupling theory using the Abaqus software in this paper; then, the failure approach index (FAI) was adopted to analyze the failure characteristics of the slope under each of the three conditions. Research results show that the influence degree of rainfall is greater than that of reservoir impoundment on the slope failure, and the influence degree of the combined effect of reservoir impoundment and rainfall is greater than that of rainfall; the sliding surface runs through only in the condition of the combined effect of reservoir impoundment and rainfall. Study results suggest that with the reservoir water level rising, the toe of the slope was gradually submerged in reservoir water and the strength of rock mass submerged by reservoir water decreased due to water-rock interaction; furthermore, the heavy rainfall was rapidly injected into the slope through the interlayer staggered zone and slope surface, the groundwater table in the middle part of the slope rose rapidly, the sliding force of the slope increased, and the stress concentration appeared at the lower part of the slope; finally, the rock bridges submerged by reservoir water in the front of the slope fractured, and the failure of the slope occurred.